Multistate outbreak of Listeria monocytogenes infections linked to whole apples used in commercially produced, prepackaged caramel apples: United States, 2014–2015. Issue 5 (9th January 2017) - ANGELO, K. M.; CONRAD, A. R.; SAUPE, A.; DRAGOO, H.; WEST, N.; SORENSON, A.; BARNES, A.; DOYLE, M.; BEAL, J.; JACKSON, K. A.; STROIKA, S.; TARR, C.; et al.
SUMMARY: Whole apples have not been previously implicated in outbreaks of foodborne bacterial illness. We investigated a nationwide listeriosis outbreak associated with caramel apples. We defined an outbreak-associated case as an infection with one or both of two outbreak strains of Listeria monocytogenes highly related by whole-genome multilocus sequence typing (wgMLST) from 1 October 2014 to 1 February 2015. Single-interviewer open-ended interviews identified the source. Outbreak-associated cases were compared with non-outbreak-associated cases and traceback and environmental investigations were performed. We identified 35 outbreak-associated cases in 12 states; 34 (97%) were hospitalized and seven (20%) died. Outbreak-associated ill persons were more likely to have eaten commercially produced, prepackaged caramel apples (odds ratio 326·7, 95% confidence interval 32·2–3314). Environmental samples from the grower's packing facility and distribution-chain whole apples yielded isolates highly related to outbreak isolates by wgMLST. This outbreak highlights the importance of minimizing produce contamination with L. monocytogenes . Investigators should perform single-interviewer open-ended interviews when a food is not readily identified.